Effect of seaweed extracts on growth and yield of rice plants - SUNARPI SUNARPI; AHMAD JUPRI; RINA KURNIANINGSIH; NUR INDAH JULISANIAH; ALUH NIKMATULLAH (Nusantara Bioscience, 2010)
Abstract. Sunarpi, Jupri A, Kurnianingsih R, Julisaniah NI, Nikmatullah A 2010. Effect of seaweed extracts on growth and yield of rice plants. Nusantara Bioscience 2: 73-77. Application of liquid seaweed fertilizers on some plant species has been reported to decrease application doses of nitrogen, phosphorus, and potassium on some crop plants, as well as stimulating growth and production of many plants. It has been reported that there are at least 59 species of seaweeds found in the coastal zone of West Nusa Tenggara Province, 15 of those species weres able to stimulate germination, growth, and production of some horticultural and legume plants. This research aims to investigate the effect of seaweed extracts obtained from ten species on growth and production of rice plants. To achive the goal, seaweed (100 g per species) wasextracted with 100 mL of water, to obtain the concentration of 100%. Seaweed extract (15%) was sprayed into the rice plants during vegetative and generative stages. Subsequently, the growth and yield parameters of rice plants were measured. The results showed that extracts of Sargassum sp.1, Sargassum sp.2, Sargassum polycistum, Hydroclathrus sp., Turbinaria ornata, and Turbinaria murayana, were able to induce growth of rice plants. However, only the Hydroclathrus sp. extract could enhance both growth and production of rice plants.